2008
DOI: 10.1158/1535-7163.mct-08-0578
|View full text |Cite
|
Sign up to set email alerts
|

Role of repair protein Rad51 in regulating the response to gefitinib in human non-small cell lung cancer cells

Abstract: Gefitinib (Iressa, ZD1839) is a selective epidermal growth factor receptor tyrosine kinase inhibitor that can block growth factor-mediated cell proliferation and extracellular signal-regulated kinases 1/2 (ERK1/2) activation. Highlevel Rad51 expression has been reported in chemoresistant or radioresistant carcinomas. In this study, we examined the role of Rad51 in regulating the response to gefitinib among different human lung cancer cell lines. The H520 line (human squamous cell carcinoma) was less sensitive … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 37 publications
(26 citation statements)
references
References 48 publications
1
24
1
Order By: Relevance
“…In lung cancer, high expression of Rad51 in tumor tissue is associated with an unfavorable prognosis (24). Our recent study has shown that the polycyclic hydrocarbon carcinogen benzo(a)pyrene can enhance the expression of Rad51 through the activation of ERK1/2 (45), and MEK1/2-ERK1/2 is the upstream signaling pathway to regulate the Rad51 expression, which is associated with the resistance to gefitinib, mitomycin C, and cisplatin in NSCLC (25,26).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In lung cancer, high expression of Rad51 in tumor tissue is associated with an unfavorable prognosis (24). Our recent study has shown that the polycyclic hydrocarbon carcinogen benzo(a)pyrene can enhance the expression of Rad51 through the activation of ERK1/2 (45), and MEK1/2-ERK1/2 is the upstream signaling pathway to regulate the Rad51 expression, which is associated with the resistance to gefitinib, mitomycin C, and cisplatin in NSCLC (25,26).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, erlotinib-enhanced Rad51 protein instability is through 26S proteasome-mediated proteolysis in H1650 and A549 cells. Our previous studies indicated that MKK1/2-ERK1/2 signaling pathway is the upstream molecules to maintain the cellular Rad51 protein and mRNA levels in NSCLC cells (26). To determine whether activation of the PI3K-AKT signaling pathway was also involved in the maintaining of Rad51 protein and mRNA expression, the NSCLC cell lines were treated with various concentrations of PI3K inhibitors, wortmannin, or LY294002.…”
Section: Erlotinib Enhances Rad51 Protein Instability Through the Degmentioning
confidence: 99%
See 1 more Smart Citation
“…First, ErbB-1 was found to directly interact with DNA-dependent protein kinase, catalytic subunit (Bandyopadhyay et al, 1998;Huang and Harari, 2000;Dittmann et al, 2005a,b;Das et al, 2006Das et al, , 2007, which is essential in the repair of DNA double strand breaks by nonhomologous end-joining (Khanna and Jackson, 2001). Second, ErbB-1 induces the expression of DNA repair genes such as XRCC1 (base-excision repair) through the Ras/Raf/MAPK pathway (Yacoub et al, 2001;Brem and Hall, 2005;Toulany et al, 2008) and Rad51 (involved in homologous recombination repair of double strand breaks) (Chinnaiyan et al, 2005;Ko et al, 2008). Third, ErbB-1 signaling modulates the activation of several DNA repair proteins, which includes DNA-dependent protein kinase, catalytic subunit (Toulany et al, 2006), and ATM (Golding et al, 2007).…”
Section: Evasion Of Immune Destruction (H-iv)mentioning
confidence: 99%
“…Plasmid transfection of MKK1-CA (a constitutively active form of MKK1, ⌬N3/S218E/S222D) and MKK2-CA (a constitutively active form of MKK2, ⌬N4/S222E/S226D) was achieved as described previously (Ko et al, 2008b). Exponentially growing human lung cancer cells (10 6 ) were plated for 18 h before exposure to emodin and MMC for 24 h in RPMI 1640 complete medium.…”
Section: Methodsmentioning
confidence: 99%